Variation in specific gravity and fibre morphology of buluh galah (bambusa heterostachya) / Jamaludin Kasim … [et al.] - Kasim, Jamaludin; Ahmad, Abd. Jalil; Mohmod, Abd. Latif; Abd. Kadir, Roszaini (Universiti Teknologi MARA Cawangan Pahang, 1994)
This paper highlights the effects of age and culm height on specific gravity and fibre morphology of Bambusa heterostachya. The specific gravity of B. heterostachya was observed to increase significantly with maturity but not with culm height. Fibre dimensions, on the other hand, varied significantly with age and culm height (except for the fibre length).